Method for synthesizing multifunctional hyperbranched copolymer through one-pot method
The multifunctional hyperbranched copolymer was synthesized by one pot method, and the P-N group was introduced onto the hyperbranched polyethylene side substrate, which solved the problem of insufficient processing fluidity and flame retardant effect of the hyperbranched copolymer, and achieved efficient and environmentally friendly flame retardant performance improvement.
Patent Information
- Application Number
- CN202510432381.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-08
- Publication Date
- 2025-07-18
AI Technical Summary
In the prior art, the processing fluidity of the hyperbranched copolymer is insufficient, and the compatibility of the phosphorus-nitrogen (P-N)-based flame retardant in the polymer is insufficient, resulting in poor flame retardant effect and difficult to meet the requirements of high-temperature processing and environmental protection.
Multifunctional hyperbranched copolymer was synthesized by a one-pot method, P-N groups were introduced onto the hyperbranched polyethylene side groups, forming HBPE@PAEEPA, and a hyperbranched copolymer with flame retardant properties was prepared using a Pd-diimine catalyst to react under ethylene pressure.
It improves the processing fluidity and flame retardant properties of the polymer, reduces processing difficulty, meets safety standards, and achieves environmentally friendly and efficient flame retardant effects.
Smart Images

Figure CN120329467A_ABST
Abstract
Description
Technical Field
[0003] The present invention relates to the field of synthesis of hyperbranched polymers, and particularly to a method for synthesizing a multifunctional hyperbranched copolymer by a one-pot method. Background Art
[0005] In modern materials science, the processing fluidity of polymers is crucial for their application performance. Especially during high-temperature processing, insufficient fluidity can lead to molding defects and low processing efficiency. Therefore, the research and development of additives that can improve the processing fluidity of polymers has become an important topic.
[0006] Hyperbranched copolymers (HBP) show broad application prospects in fields such as plastic processing, coatings, and composite materials due to their unique structures and excellent flow properties. By controlling the synthesis conditions and monomer composition, hyperbranched copolymers with specific fluidity and mechanical properties can be designed to meet different industrial requirements. The research on this technology not only promotes the development of new materials but also provides new ideas for improving processing technologies. Hyperbranched copolymers have a highly branched structure, which weakens the interaction between molecular chains, thereby reducing the viscosity of the melt. This material shows good application prospects in multiple fields such as coatings, plastics, and composite materials. Therefore, developing a new functional hyperbranched copolymer that can not only improve processing fluidity but also meet the requirements of environmental protection and economy has important market value and application potential.
[0007] At the same time, the flame retardant performance of polymers is crucial, especially in fields such as construction, electronics, and transportation. Currently, commonly used flame retardants are mainly divided into two categories: organic and inorganic. Organic flame retardants include halogen-containing flame retardants, phosphorus-based flame retardants, nitrogen-based flame retardants, etc., while inorganic flame retardants include aluminum hydroxide, magnesium hydroxide, expanded graphite, etc. Among them, halogen-containing flame retardants have been widely used due to their excellent flame retardant effects, but they will produce a large amount of toxic and corrosive gases and smoke during combustion, causing serious harm to the environment and human health. Therefore, the development of halogen-free flame retardants has become one of the main research directions in the current field of flame retardant technology.
[0008] Phosphorus-nitrogen (P-N)-based flame retardants have gradually attracted attention because they form a stable carbon layer during combustion, effectively inhibiting the release of heat and combustible gases. However, the compatibility of P-N-based flame retardants in polymers is insufficient, often resulting in their migration and loss during use, reducing the flame retardant effect. Therefore, chemically incorporating P-N groups into the polymer chain is an effective strategy to improve their flame retardant efficiency.
[0009] Hyperbranched copolymers exhibit good physical and chemical properties due to their highly branched structure, good solubility, and abundant chemical functionalization sites. By introducing P-N groups into hyperbranched copolymers, efficient flame retardant effects can be achieved while improving the mechanical properties and thermal stability of the materials. This synthesis method not only provides new ideas for the development of flame retardant additives but also may bring broader application prospects in the application of polymer materials.
[0010] Therefore, developing a method for synthesizing P-N multifunctional hyperbranched copolymers as additives to improve fluidity and flame retardancy has important theoretical significance and practical application value. Summary of the Invention
[0012] The purpose of this application is to provide a method for synthesizing multifunctional hyperbranched copolymers by a one-pot method. The advantages of this method are simple operation, low cost, mild preparation conditions, environmental friendliness, and the ability to apply a variety of polymer materials.
[0013] To achieve the above invention purpose, the present invention adopts the following technical solutions:
[0014] A method for synthesizing multifunctional hyperbranched copolymers by a one-pot method, comprising the following steps:
[0015] (a) Dissolve phenyl dichlorophosphate and triethylamine in dichloromethane to form a blended solution, and control the temperature at 0°C - 5°C.
[0016] (b) Dropwise add hydroxyethyl acrylate dissolved in dichloromethane, stir and react at 600 rpm for 3 h, then dropwise add diethylamine dissolved in dichloromethane, and stir and react at 600 rpm for 3 h.
[0017] (c) Raise the temperature to 20°C and continue to react for 10 h, then end the reaction.
[0018] (d) Filter the product in step (c), extract and separate the liquid, and remove the solvent by vacuum distillation to obtain a brown viscous liquid, which is the product AEEPA.
[0019] (e) Dissolve the product in step (d) and the catalyst Pd-diimine in dichloromethane, react under an ethylene pressure of 0.1 Mpa in the dark for 24 h, and then remove the excess solvent to obtain the final product HBPE@PAEEPA.
[0020] Among them, the molar ratio of added hydroxyethyl acrylate to phenyl dichlorophosphate is 0.5:1, the molar ratio of diethylamine to phenyl dichlorophosphate is 0.5:1, and the molar ratio of added triethylamine to phenyl dichlorophosphate is 1:1.
[0021] The filtration, extraction and liquid separation, and solvent removal by vacuum distillation in step (d) are as follows: wash with saturated NaCl solution three times, then add anhydrous sodium sulfate to remove the moisture in the product, and finally evaporate the solvent by rotary evaporation to obtain the brown viscous liquid AEEPA.
[0022] The removal of the excess solvent in step (e) means that after drying the product, add tetrahydrofuran (THF) to just dissolve the product, add 6 drops of concentrated HCl and 6 drops of H2O2, stir until the solution turns orange (about 3 h), then transfer it to a centrifuge tube, add methanol to completely precipitate the product, remove the supernatant, and blow-dry the product with cold air (repeat the above operation three times). The product is dried under vacuum at 60 °C to dryness (about 72 h) to obtain the yellow semi-fluid product HBPE@PAEEPA, and its structural formula is: 。
[0023] Preferably, the molar ratio of triethylamine to phenyl dichlorophosphate added in step (a) can be 1.2:1.
[0024] Preferably, in step (c), the final reaction temperature can be set at 25 °C to make the reaction more active.
[0025] In step (e) of the present invention, preferably, after the product is completely precipitated, it can be centrifuged (4000 rpm, centrifugation time 5 min), and then the supernatant can be removed, which can improve the yield.
[0026] Preferably, the optimal feeding ratio of AEEPA in step (e) is 0.6 mol / L.
[0027] The basic reaction principle of the present invention is:
[0028]
[0029]
[0030]
[0031]
[0032] The purpose of the present invention is to graft a P-N group on the side chain of hyperbranched polyethylene to form a multifunctional hyperbranched polymer. This synthesis method can not only effectively introduce the flame retardant group into hyperbranched polyethylene, thereby enhancing the flame retardant performance, but also improve the mechanical properties and thermal stability of the material as an additive, and has very important application prospects.
[0033] In the above technical solution, the functions of HBPE@PAEEPA mainly include: Hyperbranched polymers are three-dimensional macromolecules with highly branched structures, spherical in shape, and have low melt viscosities. When blended with engineering plastics, they can significantly improve the melt fluidity of materials, making them easy to process and form.
[0034] HBPE@PAEEPA in the present invention is a spherical polymer with flame retardant groups at its ends, having excellent flame retardant properties and thermal conductivity. Due to the P-N structure, HBPE@PAEEPA decomposes upon heating to release N gas. The N-containing compounds reduce the volatilization of P and increase the oxidation of P, generating a carbon layer and non-combustible and incombustible gases such as NH3 and H2O in the condensed phase and gas phase respectively. It can effectively dilute the O2 content in the air, weaken the combustion-supporting effect of O2, and P is thermally converted into polyphosphoric acid, poly metaphosphoric acid, etc., which can effectively promote carbonization, generate a dense carbonized layer, have a good barrier effect, prevent heat exchange, the propagation of O2, suppress smoke, etc., and can prevent molten droplets from dripping and stop the spread of flames. Moreover, the unique P-N structure of this hyperbranched copolymer has a synergistic flame retardant effect.
[0035] In the present invention, due to the positive effects of HBPE@PAEEPA, the addition amount will also affect the yield of the final product. Preferably, the optimal addition amount of AEEPA is 0.6 mol / L, and the addition amount of anhydrous dichloromethane is 20 mL. At this time, the grafting rate and yield of the final product are the best.
[0036] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: The method is simple, easy to operate, has mild preparation conditions, is environmentally friendly, can produce a hyperbranched polyethylene copolymer with flame retardant functions and improved processing fluidity, enabling it to be used as an additive in the processing field and for improving flame retardancy. This method can effectively improve the flame retardant properties of polymers and also reduce the difficulties during processing, meeting the increasingly strict safety standards. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings required to be used in the embodiments of the present application. It should be understood that the following drawings only show some embodiments of the present application and should not be regarded as limiting the scope. For those of ordinary skill in the art, without creative efforts, other relevant drawings can also be obtained based on these drawings.
[0039] Figure 1 1H NMR spectrum of AEEPA obtained in Example 1 of the present invention 1 H spectrum.
[0040] Figure 2The AEEPA infrared absorption spectrum obtained in Example 1 of the present invention.
[0041] Figure 3 The HBPE@PAEEPA nuclear magnetic 1 H spectrum obtained in Example 1 of the present invention.
[0042] Figure 4 The HBPE@PAEEPA infrared absorption spectrum obtained in Example 1 of the present invention.
[0043] Figure 5 The comparison chart of the vertical burning test results of Example 2 and Comparative Example 3 of the present invention.
[0044] Figure 6 The comparison chart of the limiting oxygen index of Example 2 and Comparative Example 3 of the present invention.
[0045] Figure 7 The comparison chart of the vertical burning test results of Example 2 and Comparative Example 4 of the present invention.
[0046] Figure 8 The comparison chart of the limiting oxygen index of Example 2 and Comparative Example 4 of the present invention. Detailed implementation manners
[0048] To make the objectives, technical solutions, and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below. For those not specified in the embodiments, the conventional conditions or the conditions recommended by the manufacturer are followed. For the reagents or instruments not specified by the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0049] 1. Sample preparation
[0050] Example 1
[0051] a: Dissolve phenyl dichlorophosphate (0.1 mol) in 40 ml of anhydrous dichloromethane, and then inject it into a three-necked flask equipped with a thermometer, a constant pressure dropping funnel, and a magnetic stirrer using a syringe. After cooling the mixture to about 0-5 °C in an ice-methanol bath, add triethylamine (0.12 mol) to the reaction system. After stirring for 30 min to mix evenly, dissolve 2-hydroxyethyl acrylate (0.05 mol) in 10 ml of anhydrous dichloromethane, and then inject it into the constant pressure dropping funnel. Control the dropping rate and finish dropping within 2 h, and then stir at a constant temperature for 3 h. Subsequently, dissolve diethylamine (0.05 mol) in 10 ml of anhydrous dichloromethane, inject it into the constant pressure dropping funnel, and then react at a constant temperature for 3 h. Finally, heat the system to 20 °C and stir for another 10 h to ensure complete reaction. After suction filtration and extraction, the solvent is removed under reduced pressure, and then washed with saturated sodium chloride solution to obtain a viscous brown liquid AEEPA.
[0052] b: Add 250 mg of Pd - diimine, 20 ml of anhydrous dichloromethane, and 0.012 mol of AEEPA (concentration: 0.6 mol / L) prepared in the above step (a) into a Schlenk flask. The ethylene pressure is 0.1 Mpa, and the temperature of the water bath is 25 °C. React for 24 h. After the reaction is completed, expose the reaction solution to air to terminate the polymerization, and blow it dry with cold air. Then add THF (about 10 mL) to just dissolve the product, add 6 drops of concentrated HCl and 6 drops of H2O2, stir until the solution turns orange - yellow (about 3 h), then transfer it to a centrifuge tube, add methanol (about 45 mL) to completely precipitate the product, remove the supernatant, and blow the product dry with cold air (repeat the above operation 3 times). Vacuum - dry the product at 60 °C until dry (about 72 h) to obtain a yellow semi - fluid product HBPE@PAEEPA.
[0053] Comparative Example 1:
[0054] Add 250 mg of Pd - diimine, 20 ml of anhydrous dichloromethane, and 0.016 mol of AEEPA (concentration: 0.8 mol / L) prepared in the above step (a) into a Schlenk flask. The ethylene pressure is 0.1 Mpa, and the temperature of the water bath is 25 °C. React for 24 h. After the reaction is completed, expose the reaction solution to air to terminate the polymerization, and blow it dry with cold air. Then add THF (about 10 mL) to just dissolve the product, add 6 drops of concentrated HCl and 6 drops of H2O2, stir until the solution turns orange - yellow (about 3 h), then transfer it to a centrifuge tube, add methanol (about 45 mL) to completely precipitate the product, remove the supernatant, and blow the product dry with cold air (repeat the above operation 3 times). Vacuum - dry the product at 60 °C until dry (about 72 h) to obtain a yellow semi - fluid product HBPE@PAEEPA.
[0055] Comparative Example 2:
[0056] Add 250 mg of Pd - diimine, 20 ml of anhydrous dichloromethane, and 0.02 mol of AEEPA (concentration: 1.0 mol / L) prepared in the above step (a) into a Schlenk flask. The ethylene pressure is 0.1 Mpa, and the temperature of the water bath is 25 °C. React for 24 h. After the reaction is completed, expose the reaction solution to the air to terminate the polymerization, and blow it dry with cold air. Subsequently, add THF (about 10 mL) to just dissolve the product, add 6 drops of concentrated HCl and 6 drops of H2O2, stir until the solution turns orange - yellow (about 3 h), then transfer it to a centrifuge tube, add methanol (about 45 mL) to completely precipitate the product, remove the supernatant, and blow the product dry with cold air (repeat the above operation 3 times). Dry the product under vacuum at 60 °C until dry (about 72 h) to obtain a yellow semi - flowable product HBPE@PAEEPA.
[0057] Example 2
[0058] Step 1: Measure 200 mg of HBPE@PAEEPA (Example 1), 2 g of ODA (diaminodiphenyl ether), and 2.2 g of BPDA (the mass ratio of ODA to BPDA is 1:1.1), add them into a sample bottle, and finally add 40 mL of DMAc (dimethylacetamide). Stir at 0 - 5 °C for 4 h. After mixing evenly, put the mixture into a vacuum degassing machine and vacuum degas at a rotation speed of 1800 rpm at room temperature for 5 min to remove the bubbles and solvents in the mixture.
[0059] Step 2: Pour the mixture into the sample groove of a polytetrafluoroethylene mold (the sample groove is a cuboid with dimensions of 125 mm×13 mm×1.6 mm and 80 mm×10 mm×4 mm), place it in a muffle furnace, and keep it at 100, 150, 200, 250, and 300 °C for 2 h respectively. The heating time for each temperature stage is 30 min. After the thermal imidization is completed and cooled to room temperature, a vertical combustion composite spline and a limiting oxygen index composite spline are obtained respectively.
[0060] Comparative Example 3
[0061] Step 1: Measure 2 g of ODA and 2.2 g of BPDA (the mass ratio of ODA to BPDA is 1:1.1), add them into a sample bottle, and finally add 40 mL of DMAc. Stir at 0 - 5 °C for 4 h. After mixing evenly, put the mixture into a vacuum degassing machine and vacuum degas at a rotation speed of 1800 rpm at room temperature for 5 min to remove the bubbles and solvents in the mixture.
[0062] Step 2: Pour the mixed solution into the sample groove of the polytetrafluoroethylene mold (the sample groove is a cuboid with dimensions of 125 mm×13 mm×1.6 mm and 80 mm×10 mm×4 mm), place it in a muffle furnace, and keep it at 100, 150, 200, 250, and 300 °C for 2 h respectively. The heating-up time for each temperature stage is 30 min. After the thermal imidization is completed and cooled to room temperature, a vertical combustion composite spline and a limiting oxygen index composite spline are obtained respectively.
[0063] Comparative Example 4
[0064] Step 1: Measure 100 mg of HBPE@PAEEPA (Example 1), 2 g of ODA, and 2.2 g of BPDA (the molar ratio of ODA to BPDA is 1:1.1), add them to a sample bottle, and finally add 40 mL of DMAc. Stir at 0 - 5 °C for 4 h. After mixing evenly, put the mixed solution into a vacuum degassing machine and vacuum degas at a rotation speed of 1800 rpm at room temperature for 5 min to remove the bubbles and solvents in the mixed solution.
[0065] Step 2: Pour the mixed solution into the sample groove of the polytetrafluoroethylene mold (the sample groove is a cuboid with dimensions of 125 mm×13 mm×1.6 mm and 80 mm×10 mm×4 mm), place it in a muffle furnace, and keep it at 100, 150, 200, 250, and 300 °C for 2 h respectively. The heating-up time for each temperature stage is 30 min. After the thermal imidization is completed and cooled to room temperature, a vertical combustion composite spline and a limiting oxygen index composite spline are obtained respectively.
[0066] 2. Characterization and Testing
[0067] (1) Nuclear Magnetic Resonance Spectroscopy Analysis (1HNMR)
[0068] The test is carried out using an AVANCEIII 500 MHz nuclear magnetic resonance spectrometer (Bruker, Switzerland). The test is carried out at room temperature, the solvent used is deuterated chloroform (CDCl3), the concentration of the substance to be tested is 20 mg / mL, and the number of scans is 16 times.
[0069] (2) Fourier Transform Infrared Spectroscopy Analysis (FTIR)
[0070] Infrared spectroscopy analysis is carried out using a Nicolet iS50 Fourier transform infrared spectrometer (ThermoFisher, USA). The attenuated total reflection infrared method (ATR) is used to analyze the substance to be tested, and the scanning wavelength range is 4000–400 cm -1 , with a resolution of 4 cm -1 , and the number of scans is 32 times.
[0071] (3) Vertical combustion (UL-94) test
[0072] The vertical combustion test was carried out using an HVUL2 type vertical combustion test system (ATLAS, USA). During the test, referring to GB / T 2408 "Determination of combustion properties of plastics - Horizontal and vertical methods", the sample specification was 125 mm × 13 mm × 1.6 mm, and each sample was tested 5 times.
[0073] (4) Limiting oxygen index test
[0074] The limiting oxygen index of the samples was determined using a JB-3 type oxygen index meter (Jiabin, China). During the test, referring to GB / T 2406.2 "Determination of combustion behavior by oxygen index method" Part 2: Room temperature test, the sample specification was 80 mm × 10 mm × 4 mm, and each sample was tested 5 times.
[0075] 3. Comparison and analysis of test results
[0076] Figure 1 1H NMR spectrum of AEEPA obtained in step (a) of Example 1. From the chemical shifts in the figure, it can be seen that: δ 7.1 - 7.3 (5H, aromatic proton), 6.4 and 5.8 (2H, vinyl), 6.1 (1H, CH=CH2), 4.4 (2H, -COO-CH2-), 4.2 (2H, P-O-CH2-), 3.1 (4H, -CH2CH3), 1.06 (6H, -CH3). 1 H spectrum. From the chemical shifts in the figure, it can be seen that: δ 7.1 - 7.3 (5H, aromatic proton), 6.4 and 5.8 (2H, vinyl), 6.1 (1H, CH=CH2), 4.4 (2H, -COO-CH2-), 4.2 (2H, P-O-CH2-), 3.1 (4H, -CH2CH3), 1.06 (6H, -CH3).
[0077] Figure 2 Infrared absorption spectrum of AEEPA obtained in step (a) of Example 1 of the present invention. From the analysis of the characteristic peaks in the figure, it can be known that the absorption peaks appearing at 2973 cm -1 、1724 cm -1 、1638 cm -1 、1636 cm -1 、1260 cm -1 are the stretching vibration peaks of -CH3, C=O, C=C, C=C on the benzene ring and P=O respectively.
[0078] Figure 3 1H NMR spectrum of HBPE@PAEEPA obtained in step (b) of Example 1 of the present invention. From the chemical shifts, it can be seen that δ 1.20 - 0.8 are the methyl, methylene and methine peaks on the hyperbranched skeleton, δ 7.2 is the peak on the benzene ring, and δ 4.4 - 4.2 are the methylene peaks on the copolymer. 1 From the chemical shifts, it can be seen that δ 1.20 - 0.8 are the methyl, methylene and methine peaks on the hyperbranched skeleton, δ 7.2 is the peak on the benzene ring, and δ 4.4 - 4.2 are the methylene peaks on the copolymer.
[0079] Figure 4This is the infrared absorption spectrum of HBPE@PAEEPA obtained in step (b) of Example 1 of the present invention. It can be analyzed from the characteristic peaks in the figure that 1724 cm -1 is the stretching vibration peak of C=O, and 1271 cm -1 is the stretching vibration peak of P=O.
[0080] Figure 5 Figure for comparing the vertical burning (UL-94) test results of Example 2 and Comparative Example 3. Among them, Figure 5 (a) is the vertical burning (UL-94) test result diagram of Example 2, Figure 5 (b) is the vertical burning (UL-94) test result diagram of Comparative Example 3. It can be seen from the figure that the prepared HBPE@PAEEPA / PI composite material can self-extinguish within 1 s after ignition, and still maintains a high self-extinguishing speed during the second ignition, without the occurrence of dripping. The flame retardant effect is excellent and belongs to V-0 level flame retardant.
[0081] It is difficult for the PI prepared in Comparative Example 3 to self-extinguish after ignition, and its flame retardant performance is poor. This shows that the HBPE@PAEEPA polymer can significantly improve the flame retardant performance of the PI material.
[0082] Figure 6 Figure for comparing the limiting oxygen index of Example 2 and Comparative Example 3. It can be intuitively seen that compared with Comparative Example 3, the limiting oxygen index of Example 2 is 30.09% higher, which can also indirectly reflect that the HBPE@PAEEPA polymer has excellent effects as a flame retardant.
[0083] Figure 7 Figure for comparing the vertical burning test results of Example 2 and Comparative Example 4. Among them Figure 7 (a) is the vertical burning (UL-94) test result diagram of Example 2, Figure 7 (b) is the vertical burning (UL-94) test result diagram of Comparative Example 4. It can be seen from the figure that the prepared HBPE@PAEEPA / PI composite material in Example 2 can self-extinguish within 1 s after ignition, and still maintains a high self-extinguishing speed during the second ignition, without the occurrence of dripping. The flame retardant effect is excellent and belongs to V-0 level flame retardant.
[0084] The HBPE@PAEEPA / PI composite material prepared in Comparative Example 4 can self-extinguish within 13 s after the first ignition, and will self-extinguish within 11 s during the second ignition, still maintaining a high self-extinguishing speed, without the occurrence of dripping. Its flame retardant performance is not as good as that of Example 2, but there is still a large improvement compared with Comparative Example 3, belonging to V-1 level flame retardant.
[0085] Figure 8It is the comparison chart of the limiting oxygen index of Example 2 and Comparative Example 4. It can be intuitively seen that compared with Comparative Example 4, the limiting oxygen index of Example 2 is 21.12% higher, which can also indirectly reflect that with the increase in the content of hyperbranched polymer, the improvement of the flame retardant performance of the PI composite material is more obvious.
[0086] The above are only the embodiments of the present application and are not used to limit the protection scope of the present application. For those skilled in the art, various changes and modifications can be made to the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for synthesizing a multifunctional hyperbranched copolymer by a one-pot method, characterized in that: It includes the following steps: (a) Dissolve phenyl dichlorophosphate and triethylamine in dichloromethane to form a blend solution, and control the temperature at 0°C to 5°C; (b) Dropwise add 2-hydroxyethyl acrylate dissolved in dichloromethane, stir and react at 600 rpm for 3 h, and then dropwise add diethylamine dissolved in dichloromethane, stir and react at 600 rpm for 3 h; (c) Raise the temperature to 20°C and continue to react for 10 h, and then end the reaction; (d) Filter the product in step (c), extract and separate the liquid, and remove the solvent by vacuum distillation to obtain a brown viscous liquid, which is the product AEEPA; (e) Dissolve the product in step (d) and the catalyst Pd - diimine in dichloromethane, react under an ethylene pressure of 0.1 Mpa in the dark for 24 h, and then remove the excess solvent to obtain the final product HBPE@PAEEPA, whose structural formula is ; Among them, the molar ratio of the added 2-hydroxyethyl acrylate to phenyl dichlorophosphate is 0.5:1, the molar ratio of diethylamine to phenyl dichlorophosphate is 0.5:1, and the molar ratio of the added triethylamine to phenyl dichlorophosphate is 1:
1.
2. The method for synthesizing a multifunctional hyperbranched copolymer by a one-pot method according to claim 1, characterized in that: The dropping rate of 2-hydroxyethyl acrylate in step (b) is 1 mL / min.
3. A method for synthesizing a multifunctional hyperbranched copolymer by a one-pot method according to claim 1, characterized in that: The dropping rate of diethylamine in step (b) is 1 mL / min.
4. A method for synthesizing a multifunctional hyperbranched copolymer by a one-pot method according to claim 1, characterized in that: The operations of filtering, extracting and separating the liquid, and removing the solvent by vacuum distillation in step (d) are to wash with saturated NaCl solution three times, then add anhydrous sodium sulfate to remove the water in the product, and finally rotary evaporate to dry the solvent to obtain a brown viscous liquid AEEPA.
5. A method for synthesizing a multifunctional hyperbranched copolymer by a one-pot method according to claim 1, characterized in that: (e) Removing the excess solvent means that after drying the product, add tetrahydrofuran to just dissolve the product, add 6 drops of concentrated HCl and 6 drops of H2O2, stir until the solution turns orange-yellow, then transfer it to a centrifuge tube, add methanol to completely precipitate the product, remove the supernatant, and blow-dry the product with cold air until dry. The product is vacuum dried at 60°C until dry to obtain a yellow semi-fluid product HBPE@PAEEPA.